Egypt and the Classical World : Cross-Cultural Encounters in Antiquity - Cole, Sara E.; Spier, Jeffrey (Book collections on Project MUSE., 2022)
"This publication, the proceedings of a 2018 scholars' symposium held at the J. Paul Getty Museum in association with the exhibition Beyond the Nile: Egypt and the Classical World, synthesizes current research on cultural interactions between Egypt, Greece, and Rome from the Bronze Age to the Roman Empire"--